2006
DOI: 10.1002/j.0022-0337.2006.70.12.tb04238.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries Risk Assessment in an Educational Environment

Abstract: This study was designed to assess, retrospectively using dental records, the impact on the management of dental caries of new caries risk assessment (CRA) forms and procedures introduced into a predoctoral dental school clinic. Of 3,659 patients with a new patient visit (NPV) and baseline exam (BE) in the two-year period of July 2003 through June 2005, 69 percent (n= 2,516) had a baseline CRA. "Visible cavitation or caries into dentin by radiograph" was significantly correlated to most items included in the CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 18 publications
5
43
0
1
Order By: Relevance
“…Visible cavitation or caries into dentin identified by radiographic examination was shown to significantly correlate with several caries risk factors. 73 Caries lesions leading to restorations within a three-year period was one of the correlated items, 73 which is similar to the criteria applied in some of the included studies reporting a significant influence on restora- tion survival. 15,22,42 Although the included studies reported different methods and cutoff points (Table 1), most of them were able to show an influence of caries-related variables on restoration failure (Table 4).…”
Section: Cariesmentioning
confidence: 86%
“…Visible cavitation or caries into dentin identified by radiographic examination was shown to significantly correlate with several caries risk factors. 73 Caries lesions leading to restorations within a three-year period was one of the correlated items, 73 which is similar to the criteria applied in some of the included studies reporting a significant influence on restora- tion survival. 15,22,42 Although the included studies reported different methods and cutoff points (Table 1), most of them were able to show an influence of caries-related variables on restoration failure (Table 4).…”
Section: Cariesmentioning
confidence: 86%
“…(21) found that among Texas pediatric dentists, 39% of respondents used both verbal and written CRA's. A study at a US dental school that examined the impact of initiating the use of a CRA form found that faculty were slow to incorporate its use, but by the end of the second year, a level of 80% compliance was reached (26). The authors suggested that the faculty, some of whom may have been trained at a time when caries restoration was the standard treatment for caries, were skeptical about the importance of CRA in a caries management program.…”
Section: Discussionmentioning
confidence: 99%
“…Less‐than‐optimal treatment follow‐up after CRA has also been reported in a predoctoral teaching clinic. In this program, patients assessed as having high caries risk were supposed to receive a bacterial assessment; however, this was not followed in most cases (26). On the other hand, a study by Bader et al.…”
Section: Discussionmentioning
confidence: 99%
“…As dental caries is a multi-factorial disease, studies to explore interactions between caries risk indicators and disease occurrence are often based on multi-factorial modelling (11)(12)(13)(14). For caries, the etiologic factors are known as 'risk factors' while the non-etiologic factors as 'risk indicators' (15).…”
Section: Introductionmentioning
confidence: 99%